P4.039 HIV-Positive Client Reproductive Desires and Health Care Provider Perspectives of Pregnancy in HIV-Positive Women in eThekwini District, KwaZulu-Natal, South Africa. (13th July 2013) - Milford, C; Greener, R; Pienaar, J; Beksinska, M; Rambally, L; Drace, M; Sithole, K; Mabude, Z; Smit, J
Abstract : Background: The Province of KwaZulu-Natal, South Africa has among the highest concentrations of people living with HIV However, with improved access to ARVs and PMTCT, PLWHIV are now able to have children with minimal risk. There is therefore a need to explore current fertility and contraceptive desires of this population to ensure appropriate and accessible sexual and reproductive health (SRH) counselling. Methods: Baseline and Endline surveys were conducted in 2009 and 2011 with providers and clients at seven healthcare facilities, before and after the implementation of a SRH service integration model, in eThekwini District. HIV-positive clients' fertility intentions, contraceptive use and providers' perceptions of pregnancies among HIV-positive women were explored. Descriptive statistics were generated using SPSS. Results: At baseline 46 providers and 86 HIV-positive clients (14 male, 72 female) and at endline 44 providers and 144 HIV-positive clients (43 male, 101 female) were interviewed. 18.6% and 38% of clients at baseline and endline, respectively, wanted more children. At baseline and endline, females with HIV-positive partners were less likely than those with HIV-negative partners to want more children. Concerns about the health of the baby and self were common reasons for not wanting more children. At baseline, of those who wanted children, half the women and all men were using contraception. At endline, 80% of women and 72% of men who wanted children were using contraception. Male condoms were the most common contraceptive used. At baseline, 43% of providers thought healthy HIV-positive women could consider having children, compared with 66% at endline. Conclusion: There is a need for reproductive choices and family planning to be integrated with HIV services. Comprehensive policies and programmes should be developed to address SRH counselling needs of HIV-positive men and women, and address the values and training needs of providers.